The relationship between employees' perceptions of talent management practices and levels of engagement : a Botswana organisational case study. - Roper, Katherine (My University, 2010)
A recent trend in the business literature is the focus on the possible link between talent management efforts of an organisation and that organisation’s effectiveness. Despite this trend the evidence supporting such a link is weak. Many books and journals advocate the implementation of certain strategies to obtain the benefits proposed. However, not all these articles have foundations within empirical research, but rather the business management literature. This research report provides an empirical based research study. The novelty of the study stems from its focus on the relationship between employee engagement and employee perceptions of talent management practices within a NGO. NGOs are underutilized research contexts within the current literature. The sample for this study is from an NGO in Botswana that focuses on the mobilization of HIV testing services and has the vision of no new HIV infections in 2016. Forty-eight participants took part in the study, the majority of this sample is female (67%), the main home language is seTswana, the mean age is 32, the mean organisational tenure is four years and most participants are employed as counsellors within the organisation. Pearson correlation coefficients were calculated to examine the association between the main constructs. There was insufficient evidence to support a relationship, but the sample used in the study had high levels of employee engagement, as well as positive perceptions of the talent management practices within their organisation. Discussions of these engagement levels and perceptions of practices are present, as well as discussions of the significant relationships between the main constructs and the other measured variables. Significant relationships were found ii between employee’s perceptions of talent management and the overall number of years that employees had been working (p = .05), and between employee engagement and employee’s tenure within the organisation (p > .01). A regression was performed on the data once job position had been stratified into two groups- counsellors (42%) and office based workers (58%). A significant relationship between the main constructs was found for office based employees (R-square = 29%). The study’s results are discussed in light of the existing literature, and recommendations are made from the study’s findings. One important recommendation is for the participating organisation to consider implementing a strategy that focuses on enhancing the organisation’s counsellors’ perceptions of organisational practices and their employee engagement.